POLIGAMI DALAM PERSPEKTIF MAQASID AL-KHALQ - Anita Yulia; Jabbar Sabil (Prodi Magister Hukum Keluarga Pascasarjana UIN Ar-Raniry Banda Aceh, 2023)
In Islam, the ultimate goal of humanity is to achieve obedience and submission to Allah, in accordance with Islamic teachings. Al-Ghazali stated that the maqāṣid al-khalq encompasses objectives such as attaining happiness, fulfilling material needs, achieving personal success, obtaining inner peace, and so forth. However, in the context of Islam, the goals of humanity are not limited to these subjective aspects. Discussing the goals of humanity (Maqāṣid al-khalq) in polygamy must consider whether the intentions behind polygamy align with Shariah. Polygamy cannot be universally deemed harmful (mafsadah) because in some cases, individuals engage in polygamy with specific intentions. However, are these intentions in accordance with the requirements of maqāṣid al-syar‘iyyah? Therefore, it is necessary to analyze the principle of prioritizing the prevention of harm over the realization of benefits through the validation of the objectives of creation. The purpose of this research is to analyze the essence of polygamy from the perspective of maqāṣid al-khalq and to examine the alignment between the objectives of Shariah and the objectives of creation in the context of polygamy law. This type of research is normative and also known as library research. The results of this study are: firstly, based on the validity of Maqāṣid al-khalq, it proves that there are numerous beneficial effects generated. This is in line with the four stages of tarjih which do not contradict the provisions of al-maqāṣid al-syar‘iyyah. Secondly, the discourse of Allah SWT is a definitive law that cannot be repealed. Therefore, when Allah establishes the permissibility of polygamy (al-maqāṣid al-syar‘iyyah), and humans engage in polygamy (maqāṣid al-khalq) in accordance with Shariah through legislative law, then the human objective (maqāṣid al-khalq) is not regarded as following one's desires.